2017
DOI: 10.3389/fmars.2017.00294
|View full text |Cite
|
Sign up to set email alerts
|

Small Scale Genetic Population Structure of Coral Reef Organisms in Spermonde Archipelago, Indonesia

Abstract: Small island archipelagos with fringing and dispersed reef systems represent special marine ecosystems, providing a patchy habitat for many coral reef organisms. Although geographic distances may be short, it is still unclear if such environments are inhabited evenly with panmictic conditions or if limited connectivity between marine populations, even on small geographic scales, leads to genetic differentiation between areas within the archipelago or even single reef structures. To study diversity patterns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
5
12
0
Order By: Relevance
“…Inbreeding in a population could cause a reduction in the heterozygosity and an increase in the homozygosity, as shown in overharvested populations (Pinsky and Palumbi, 2014). Despite dispersing larvae, A. ocellaris showed a significant genetic differentiation between the two island populations (F ST 536 = 0.065 ± 0.048, p = 0.01), which was also shown in a previous study (Timm et al, 2017). In a study on the anemonefish species A. clarkii significant F ST -values (=0.028) were found between sites on a similarly small scale in the Philippines (Pinsky and Palumbi, 2014).…”
Section: Discussion Genetic Variability and Differentiation Between Tsupporting
confidence: 83%
See 1 more Smart Citation
“…Inbreeding in a population could cause a reduction in the heterozygosity and an increase in the homozygosity, as shown in overharvested populations (Pinsky and Palumbi, 2014). Despite dispersing larvae, A. ocellaris showed a significant genetic differentiation between the two island populations (F ST 536 = 0.065 ± 0.048, p = 0.01), which was also shown in a previous study (Timm et al, 2017). In a study on the anemonefish species A. clarkii significant F ST -values (=0.028) were found between sites on a similarly small scale in the Philippines (Pinsky and Palumbi, 2014).…”
Section: Discussion Genetic Variability and Differentiation Between Tsupporting
confidence: 83%
“…This strategy prevents the loss of rare alleles from older and bigger individuals. Second, the implementation of marine protected areas (MPAs), which take into account high self-recruitment in A. ocellaris (Madduppa et al, 2014b) and the limited connectivity of populations (Timm and Kochzius, 2008;Timm et al, 2012Timm et al, , 2017. High selfrecruitment implies that the populations are more vulnerable to fishing activity (Thorrold et al, 2001).…”
Section: Implications For Management and Conservationmentioning
confidence: 99%
“…However, it is possible that one reason for this apparent lack of structure and low differentiation is the limitation of the sampling design used in this study. The results of a study on clownfishes and sea squirts in the Spermonde Islands by Timm et al (2017) found fine-scale gene flow patterns which were limited to this small scale region.…”
Section: Genetic Diversity and Connectivity Within Sulawesi Scleractimentioning
confidence: 90%
“…Geographically, Indonesia is flanked by both the Pacific Ocean and the Indian Ocean, resulting in extremely complicated flow patterns within the Indonesian archipelago. In addition to the dynamics of the Indonesian Through Flow (ITF) that moves under the thermocline layer and carries biological material from the Pacific Ocean to the Indian Ocean (Timm et al 2017), complex surface flows also become a transportation medium for marine organisms whose dispersal and/or settlement phases take place in shallow waters.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used genetics to infer patterns of larval dispersal within Indonesia (Barber et al 2000(Barber et al , 2002(Barber et al , 2006Timm et al 2017;DeBoer and Barber 2010;Crandall et al 2010). These studies typically identify three unique regions: (i) Western Indonesia, including Sumatera, and Java, (ii) Central Indonesia including the Lesser of Sunda Islands, Sulawesi, and Sangihe-Talaud, and (iii) Eastern Indonesia, including Halmahera and West Papua Carpenter et al 2011).…”
Section: Introductionmentioning
confidence: 99%